2019
DOI: 10.1016/j.heliyon.2019.e02657
|View full text |Cite
|
Sign up to set email alerts
|

Estimating confined aquifer parameters using a simple derivative-based method

Abstract: The confined aquifer parameters, transmissivity and storage coefficient, are commonly determined using the pumping tests. Several methods have been developed to estimate confined aquifer parameters using pumping tests, but different methods suffer from different drawbacks. Those methods that use the truncated Theis well functionwtrue(utrue), apply just early or late drawdowns, depending on the case, to estimate the aquifer parameters. Those methods, such as Theis (1935), that use non-truncated well functionwtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…MAE and RMSE values were mostly comparable with those of Alzraiee et al (2014) with exception of those of borehole H27-0165 and H27-0290 which were higher. The RMSE values computed from measured and drawdowns estimated from simple derivative-based and curve type methods for a confined aquifer located in Fars province, southern Iran ranged from 0.091 to 0.82 m in a study conducted by Naderi (2019). The RMSE values for four boreholes (H27-0002, H27-0052, H27-0136 and H27-0138) were within the range of values obtained by Naderi (2019).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…MAE and RMSE values were mostly comparable with those of Alzraiee et al (2014) with exception of those of borehole H27-0165 and H27-0290 which were higher. The RMSE values computed from measured and drawdowns estimated from simple derivative-based and curve type methods for a confined aquifer located in Fars province, southern Iran ranged from 0.091 to 0.82 m in a study conducted by Naderi (2019). The RMSE values for four boreholes (H27-0002, H27-0052, H27-0136 and H27-0138) were within the range of values obtained by Naderi (2019).…”
Section: Discussionmentioning
confidence: 52%
“…The RMSE values computed from measured and drawdowns estimated from simple derivative-based and curve type methods for a confined aquifer located in Fars province, southern Iran ranged from 0.091 to 0.82 m in a study conducted by Naderi (2019). The RMSE values for four boreholes (H27-0002, H27-0052, H27-0136 and H27-0138) were within the range of values obtained by Naderi (2019). Fan et al (2020) obtained RMSE values ranging from 0.124 to 5.197, 0.039 to 0.24, 0.094 to 2.627 when estimating aquifer parameters based on neural network (ANN), random forest (RF), and support vector machine (SVR) methods, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To further test the performance of the PyTheis code under different types of flow conditions, we solved the following eight different problems reported in the literature: Walton [31], Fetter and Rayne [32], Driscol [33], McWhorter and Sunda [34], Viessman and Lewis [35], Todd and Mays [36], and two sets of data from Naderi [23]. Our results indicated that the PyTheis code, with the default initial values and parameter bounds, was able to solve all eight problems.…”
Section: Resultsmentioning
confidence: 99%
“…Most automatic curve fitting tools employ a nonlinear fitting algorithm to minimize the sum of squared error between observations and model predictions [7,8,10,[21][22][23] In a recent study, Bateni et al [24] compared the performance of various nonlinear programming methods including the genetic algorithms (GA) and ant colony (AC) methods to estimate aquifer parameters using five different time-drawdown datasets. The authors concluded that both GA and AC are reliable methods for evaluating aquifer parameters, and they performed better than the graphical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Further, this study has investigated the sensitivity of the parameter estimates to different types of information loss in homogenous aquifers and has not considered spatial dependency of the aquifer parameters. In reality, of course, aquifers are typically heterogeneous and any estimated values for the aquifer parameters are representative of the average characteristics of the cone of depression at a given time during the pumping test (Naderi, 2019; Wen et al, 2010; Wu et al, 2005). Above we saw that different values for the aquifer parameters (e.g., different value of T and S in a confined aquifer), resulted in different amounts of sensitivity under the same type of information loss.…”
Section: Discussionmentioning
confidence: 99%